Comparing the effectiveness of collaborative teaching method with brain-based teaching method on students\' social competence - Elham Torabi Nia; Fatemeh Jamali; Neda Nateqi (Iranian Journal of Educational Research, 2023)
Objective: The aim of the present study was to compare the effectiveness of collaborative teaching method with brain-based teaching method on students' social competence. Methods: The statistical population consisted of students studying in the academic year 2021-2022 in the middle school level of District 2, Tehran. Then, a total of 36 students were purposefully selected and randomly assigned to three groups: collaborative teaching method group (12 students), brain-based teaching method group (12 students), and control group (12 students). In the experimental groups, collaborative teaching method and brain-based teaching method were implemented in ten 50-minute sessions. These two groups underwent training using these methods, while the control group did not receive any form of training or intervention. The data were collected using the Flener's Social Competence Questionnaire (1990). Data analysis was conducted using analysis of covariance (ANCOVA). Results: The results indicated that both collaborative teaching method and brain-based teaching method were effective on social competence. Individuals who received training using the collaborative teaching method achieved higher scores in social competence after the intervention compared to those who received training using the brain-based teaching method, demonstrating the greater efficacy of the collaborative teaching method over the brain-based teaching method. Conclusion: Educational practitioners and policymakers can use these insights to make informed decisions about teaching strategies that best serve the holistic development of students, ultimately contributing to their overall well-being and success in academic and social domains.